Environmental agreements as clubs: Evidence from a new dataset of trade provisions - Jean-Frédéric Morin; Clara Brandi; Jakob Schwab (The Review of International Organizations, 2023)
Creating intergovernmental environmental clubs is a prominent policy proposal for addressing global environmental problems. According to their proponents, environmental clubs provide an incentive to join them and accept their environmental obligations by generating exclusive “club goods” for their members. Yet, the existing literature considers environmental clubs as a theoretical idea that still has to be put into practice. This article asks whether, in fact, the numerous international environmental agreements (IEAs) containing trade-related provisions provide club goods to their parties. It does so by investigating the effects of these provisions on trade flows among parties compared to flows with non-parties. We introduce an original dataset on 48 types of trade provisions in 2,097 IEAs that we make available with the publication of this article. Based on this new data and a panel of worldwide bilateral trade flows, we find evidence that existing IEAs and their trade-liberalizing content are associated with increased trade among their parties relative to trade with non-parties. We conclude from this finding that systems of IEAs provide club goods to their parties. Uncovering the existence of environmental clubs has significant methodological and policy implications. It is an important first step for future research on the actual effectiveness of clubs in attracting participation and raising environmental standards.
Keywords: F18; F64; Q56; 320; International Environmental Agreements (IEAs); Trade and environment; Climate clubs; Club goods